Development of an automated method for analysis of environmental gamma spectra collected with HPGe detectors - Andreicovici, Iulian; Seremet, Radu; Ise, Silvia; Ujeniuc, Sorin; Pojar, Iulian; Suvaila, Rares (HNPS Advances in Nuclear Physics, 2025)
Gamma ray spectrometry is one of the most valuable tools in interdisciplinary research work based on radioactivity. Although a multitude of software packages for gamma ray spectra analysis are available on a large scale, only a few of them are oriented towards environmental applications. To improve the investigation protocol, we designed software with features meant to respond to specific needs of archaeological and geological samples. We present a newly developed program meant to enhance precision with emphasis on the low energy part of the spectrum, including features such as autocalibration, especially with a focus on high-purity germanium detectors. The software was tested against commercially available packages for calibration and environmental sample spectra, providing very good results. The algorithm proved to be robust and efficient, while using simple procedures based on the physics of the interactions of interest. Currently our team is working on adding more functions albeit keeping the program user-friendly, before making it available online.